EFEKTIVITAS APLIKASI DIGITAL WEVERSE SEBAGAI MEDIA PEMENUHAN KEBUTUHAN INFORMASI PARA PENGGEMAR K-POP DI INDONESIA - Zanah, Kolifathul; Prajawinanti, Arin (UPT Perpustakaan Universitas Bengkulu, 2025)
ABSTRACT In today's digital era, information has become a primary need in daily activities. Weverse is a social media application that is widely used to fulfill the information and communication needs between K-Pop idols and their fans. This research was conducted to determine the effectiveness of the Weverse digital application as a medium for fulfilling the information needs of K-Pop fans in Indonesia. The theories used in this research are communication effectiveness from Andre Hardjana, the theory of meeting information needs from Katz, Gurevitch, Hans and new media theory from Pierre Levy. This research uses descriptive quantitative methods with observation, documentation and distributing questionnaires in the form of Google forms to K-Pop fans who actively use Weverse with 100 samples that have been determined using the Simple Random Sampling technique or samples chosen randomly. The data that has been obtained is then analyzed by carrying out validity tests, reliability tests, normality tests, linearity tests, correlation tests, F tests, T tests, and coefficient of determination. From this research, a significance value of 0.000 was obtained with the linear regression equation Y = 4.798 + 1.139X. With the calculation results of R Squere 0.818 which shows that there is an influence between variable X and variable Y of 81.8% and the remaining 18.2% is influenced by other factors. And the T test shows that there is a significant influence, which means that the use of the Weverse digital application is significantly effective in fulfilling the information needs of K-Pop fans in Indonesia Keywords: Weverse Application, Information Needs, Fans